Case Study Regarding the Identity Crisis: Array - Neculai, Loredana (New Trends in Psychology, 2021)
The crisis can be defined as an event or a complex of unexpected events, unexpected but also unplanned, generating danger to the climate, health or safety of the class and its members. The management of the class is defined by Romiță B. Iucu in the paper mentioned above, as “the optimal strategic management of the instructive-educational activity, designed and carried out in an educational unit / class of students”. School maladaptation - is defined as the set of psycho-behavioral manifestations characterized by temporary lack or difficulty in integrating or accommodating the individual to the educational social environment. I chose to analyze a case study of an A.E. from the 12th grade from the high school with a sports profile in the city, where I also do the internship, due to the specific problems of adolescence, suffers from an identity crisis, reflected in the tendency to drop out of school and leave home.